(untitled) (Revista Contexto & Educação, 2021)
The present study, carried out during the social isolation context of 2020, required by preventive measures against the covid-19, aimed to analyze the perceptions of the students who had their activities moved from the presential practice for a distance learning context. Thirteen mathematics students participated in the study, expressing themselves about the use of the Digital Information and Communication Technologies in the teaching and learning processes. The collected information was analyzed with Seymour Papert e John Dewey theories, among others, through the Discursive Textual Analysis from a deconstruction and reconstruction movement of ideas. Emerged as representative categories of student´s perceptions about the format changes imposed: Understanding and Facing Difficulties and The Need of Presential Dialogical Interaction that originated the metatexts where the weaknesses and the potentialities perceived were discussed.